2018
DOI: 10.1074/jbc.ra118.003499
|View full text |Cite
|
Sign up to set email alerts
|

Uropathogenic Escherichia coli invades bladder epithelial cells by activating kinase networks in host cells

Abstract: Uropathogenic (UPEC) is the causative bacterium in most urinary tract infections (UTIs). UPEC cells adhere to and invade bladder epithelial cells (BECs) and cause uropathogenicity. Invading UPEC cells may encounter one of several fates, including degradation in the lysosome, expulsion to the extracellular milieu for clearance, or survival as an intracellular bacterial community and quiescent intracellular reservoir that can cause later infections. Here we considered the possibility that UPEC cells secrete fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…The ExPEC prototype strains CFT073, 536, J96, and RS218 belong to phylogroup B2, and all showed the phenotypic capacity to adhere to and invade a variety of epithelial cells, survival the complement bactericidal activity, and produce biofilms [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Nevertheless, these features were expressed at different levels in clinical isolates [ 22 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ExPEC prototype strains CFT073, 536, J96, and RS218 belong to phylogroup B2, and all showed the phenotypic capacity to adhere to and invade a variety of epithelial cells, survival the complement bactericidal activity, and produce biofilms [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Nevertheless, these features were expressed at different levels in clinical isolates [ 22 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…IL6 is known as an inflammatory biomarker, while FOS, MYC, and EGFR were originally known as oncogenes. Recently, a growing number of studies have revealed that these oncogenes might play key regulation roles in inflammation and immune responses ( Wagner, 2010 ; Schonthaler et al, 2011 ; Man and Kallies, 2015 ; Kim et al, 2018 ; Fajgenbaum and June 2020 ). Therefore, the four targets may be responsible for the action of CCF against UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…In the bladder of mice lacking RNase 7 and LL-37, the UPEC communities are significantly increased (47,63). (Figure 1) Some UPEC survives from the extracellular immune responses and invades BECs, which then initiate the intracellular efflux immune responses (65,66). Once BECs are invaded, two waves of UPEC expulsion in an innate immune signaling-orchestrated process occur (67).…”
Section: Upecmentioning
confidence: 99%